Human Capital Accumulation and Economic Growth in Nigeria - Ayodele Ibrahim Shittu; Peng Xiang; Matthew Babatope Ogunniyi (Unilag Journal of Humanities, 2019)
This article examines the relationship between human capital accumulation and economic growth in Nigeria. The OLS method of estimation was used for the purpose of estimating the required parameters. Interestingly, the findings reveal that human capital accumulation has a significant and positive impact on economic growth in Nigeria. This study makes an important contribution to the literature on economic growth, particularly those that focus on African countries. We tested for the role of both structural and political institutions. While the estimate of the structural institution exhibits a significant and positive effect on economic growth, the estimate of the political institution exhibits an insignificant and negative effect on economic growth in Nigeria.